Fashion industry, innovation and intellectual property / Indústria da moda, inovação e propriedade intelectual - Basso, Maristela (Revista Online de Pesquisa : Propriedade Intelectual, 2019)
Bearing in mind the absence of specific legal norm on “fashion design” and the lack of expertise of our judges, Brazilian courts have recognized some degree of protection for designs granted by the fashion industry. They do not deny protection, as the North Americans who exclude the utilitarian aspects, nor even declare rights as vast as in French law. The trend of the judged in Brazil is in an intermediate position. That is, they aim to encourage innovation, on the one hand, and on the other, limit copying, requiring incremental elements to provide protection.